Pengembangan Pop Up Book digital Budaya Daerahku Mata Pelajaran IPAS Kelas V Sekolah Dasar - Nurul Fatmawati; Nugrananda Janattaka (EduStream: Jurnal Pendidikan Dasar, 2025)
Pop-up book digital media is a type of digital media that incorporates three-dimensional (3D) effects, helping learners enhance their overall understanding. The purpose of the study was to describe the development process, validity, and applicability of Pop-up book digital media. Using Research and development with the ADDIE model. The research subjects were fifth-grade students of elementary school students. The data collection technique used a questionnaire. Data analysis techniques using quantitative descriptive methods. The results of the research on the development of Digital Pop-up Book media on social studies for fifth grade students were carried out using the ADDIE model which includes Analyze (problem and needs analysis), Design (design of making Digital Pop-up Book media), Development (media validation and material validation), Implementation (small group and large group trials), Evaluation (revision of the Pop-up book digital media cover). The score of media validation results obtained a percentage of 94.16% with the category “very valid”. Material expert validation obtained a percentage of 92.5% in the “very valid” category. The applicability of Pop-up book digital media in small groups has a percentage of 85.76% and the results of large group trials obtained a percentage of 88.8% so as to obtain a “very good” category. Pop-up book digital media proved to be very valid and very good to help stimulate students in the learning process.